(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The aim of the present study was used to develop SSR markers and to determine genetic relationships among Asparagus species and its cultivars. We mined 72953 Asparagus nucleotide sequences from NCBI and were analyzed. In total, 143 SSRs from 1943 SSRs containing sequences were identified. Of these, 13.6 % were dinucleotide repeats and 2.3 % were trinucleotide repeats. The most frequent dinucleotide repeat motif was AA/TT (73.9 %). The percentage of tri-nucleotide motifs was highest which coded for stop codon (36 %), whereas the Glycine was least present (4.5%). Among the total of 14 SSR primers used, 10 markers yielded 144 (92.3 %) polymorphic bands with an average of 14.4 alleles per primer. Cluster analysis based on UPGMA grouped the Asparagus species and its cultivars into two main clusters. Cluster A contained only A. grecilius which is more diverse than others, while cluster B was further clustered into two sub clusters. Cluster I was comprised of Asparagus officinalis cultivars and cluster II was comprised of Asparagus wild species. Furthermore, these primers (42.8%) were found to be transferable in other medicinal plants (Curcuma longa L. and Saussurea costus). The results suggest that SSR markers are sufficiently useful and powerful to assess genetic relationships and diversity analysis in Asparagus and A. officinalis cultivars. Furthermore, these markers will be particularly useful for evolutionary and genetic mapping studies in Asparagus. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 21-32